2020
DOI: 10.3390/pr8101272
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Combustion in 35 t/h Industrial Pulverized Coal Furnace with Burners Arranged on Front Wall

Abstract: Coal-fired industrial boilers should operate across a wide range of loads and with a higher reduction of pollutant emission in China. In order to achieve these tasks, a physical model including two swirling burners on the front wall and boiler furnace was established for a 35 t/h pulverized coal-fired boiler. Based on Computational Fluid Dynamics (CFD) theory and the commercial software ANSYS Fluent, mathematical modeling was used to simulate the flow and combustion processes under 75% and 60% load operating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…For a certain equivalence ratio, Huang et al [16] showed that the inclusion of central air could improve the flame stability and optimize the flame shape. In addition, several studies had demonstrated that increasing the central air in a swirl burner could effectively decrease the emissions of NO x [17][18][19]. For example, Xie et al [20] investigated the effect of secondary air flaring angle and central air ratio on NO x emissions of HT-NR3 burner, using a thermal test stand.…”
Section: Introductionmentioning
confidence: 99%
“…For a certain equivalence ratio, Huang et al [16] showed that the inclusion of central air could improve the flame stability and optimize the flame shape. In addition, several studies had demonstrated that increasing the central air in a swirl burner could effectively decrease the emissions of NO x [17][18][19]. For example, Xie et al [20] investigated the effect of secondary air flaring angle and central air ratio on NO x emissions of HT-NR3 burner, using a thermal test stand.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of impeller configuration and speed were reported. Han et al [4] studied the combustion performance in a pulverized coal furnace with burners installed on the front wall by coupling the momentum balance (with turbulence model), species transport, and energy balance equations. The goal was to optimize the process for reduced nitrogen emission and air pollution.…”
mentioning
confidence: 99%